Magnetic characterization of the primary state of bacterial photosynthesis - Norris, J. R. (1982)
The results of reaction yield-detected magnetic resonance (RYDMR) experiments carried out on modified bacterial photosynthetic reaction centers (RCs) are interpreted in terms of a model that assigns the initial charge-separated radical ion-pair state, P(F), as the carrier of the spectrum. The radical pair theory, which has been invoked to explain magnetic field effects in RCs, was significantly expanded to take into consideration the electron dipole-dipole interaction. It is shown that this is the largest interaction between the components of the radical ion pair. Quantum statistical calculations are described simulating the RYDMR spectra and low-field effects in quinone-depleted RCs. The experimental data on which the simulations are based are (i) the magnitude of the field effect at 3,000 G, (ii) the field at which 0.5 of the maximal field effect is observed, (iii) the P(F) population as a function of time at zero magnetic field, (iv) the RYDMR linewidth for low microwave field strength, (v) the RYDMR intensity and width as a function of microwave field, and (vi) the maximum RYDMR intensity at H(I) ≃ 2ǀJǀ. With this information it was found possible to characterize P(F) in terms of four parameters, two containing structural information and two with kinetic implications. These are the dipole-dipole interaction, D = -47 ± 10 × 10(-4) cm(-1); the exchange interaction, J = -7.5 ± 1.9 × 10(-4) cm(-1); and the inverse rate constants of the decay of the radical pair states with singlet and triplet spin functions, respectively, k(S)(-1) = 15 ± 4 nsec and k(T)(-1) = 1.8 ± 0.2 nsec. The structural and dynamic implications of these parameters are discussed.